News on the opinion and the periodic press in Córdoba autonomous province:1820-1852 (Quinto Sol, 2013)
This exploratory work seeks to answer some questions of diverse complexity related with the public opinion and the periodic press in Córdoba province between 1820 and 1852. Points selected for our study include the origin of publications, its regularity,its edition contexts and ideological and political orientation of the texts and of their publishers/editors. Political context is deemed the most important factor to explain the periodical production and the type of journalism existing.
Keywords: Journalism; periodic press; Córdoba; 19th century